Konstruksi Citra Laki-laki pada Iklan Daihatsu Ayla versi “Habis PD Terbitlah Asik” - Atsyukayanti, Putu Wela; Sugiarica Joni, I Dewa Ayu; Alit Suryawati, Gusti Agung (E-Jurnal Medium, 2021)
Advertising has an important role in a company as know as implementing various communications functions. Advertising can cause changes in the constructions of thoughts about gender stereotypes, stereotype about masculinity. This is determine the constructions of the man image that is formed in the Daihatsu Ayla advertisement version of ‘Habis PD Terbitlah Asik”. Which has a durations of 1 minute 25 seconds. Data are obtained through observation and documentations. In this study was using semiotics. The analysis show that the expression intended to be a representation of the male image is self-confidence, monologue of the male main character. On the other hand, this advertisement also illustrates that having a Daihatsu Ayla car does not necessarily change a man to follow the standards of masculinity that exist in society, however, a Daihatsu Ayla car can increase self-confidence by staying true to yourself.